Type II Toxin-Antitoxin Systems in Escherichia coli - Zhang H; Tao S; Chen H; Fang Y; Xu Y; Han AX; Ma F; Liang W (Infection and Drug Resistance)
He Zhang,1 Shuan Tao,2 Huimin Chen,2 Yewei Fang,2 Yao Xu,3 A-Xiang Han,2 Fang Ma,1,* Wei Liang2,* 1Department of Medical Laboratory, Bengbu Medical University, Bengbu, Anhui, People’s Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of China; 3School of Medicine, Ningbo University, Ningbo, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Liang, Department of Clinical Laboratory, The First Affiliated Hospital of Ningbo University, 31 Liuting Street, Ningbo, Zhejiang, People’s Republic of China, Tel +8613306652821, Fax +86-051885213100, Email hslwys@163.com Fang Ma, Department of Medical Laboratory, Bengbu Medical University, No. 2600, Donghai Avenue, Bengbu, Anhui, People’s Republic of China, Tel +8618955222802, Email 0600130@bbmc.edu.cnAbstract: The toxin-antitoxin (TA) system is widespread in prokaryotes and archaea, comprising toxins and antitoxins that counterbalance each other. Based on the nature and mode of action of antitoxins, they are classified into eight groups (type I to VIII). Both the toxins and the antitoxins are proteins in type II TA systems, and the antitoxin gene is usually upstream of the toxin gene. Both genes are organized in an operon and expression of which is regulated at the transcriptional level by the antitoxin-toxin complex, which binds the operon DNA through the DNA-binding domain of the antitoxin. The TA system plays a crucial role in various cellular processes, such as programmed cell death, cell growth, persistence, and virulence. Currently, Type II TA systems have been used as a target for developing new antibacterial agents for treatment. Therefore, the focus of this review is to understand the unique response of Type II TA in Escherichia coli to stress and its contribution to the maintenance of resistant strains. Here, we review the Type II TA system in E. coli and describe their regulatory mechanisms and biological functions. Understanding how TA promotes phenotypic heterogeneity and pathogenesis mechanisms may help to develop new treatments for infections caused by pathogens rationally.Keywords: E. coli, type II toxin-antitoxin, bacterial persistence, biofilm formation, phage infection